Diseño de un producto agroturístico, para aprovechar las potencialidades de la finca “D Lucas” en el sector San Pedro, parroquia La Esperanza, provincia de Imbabura - Obando Rojas, Santiago Andrés (2022)
The agro-tourism farm 'D Lucas' is located between San Pedro neighborhood in San Jacinto Parish ´´La Esperanza´´. It is a natural place combines with a healthy environment in the rural area, which has been used for livestock and agricultural purposes by its owners. Currently, based on the results of a situational technical diagnosis on the needs and demands population, its owners with a vision of providing and generating new options for food, recreation and the most relevant is that customers have direct contact with nature being part of it. That is why it has decided to implement an agro-tourism project to offer twelve products and services of great-unsatisfied demand from national and foreign tourists\; Furthermore, this study aims to motivate and encourage the healthy food consumption and at the same time enjoy doing different recreation activities, always focusing on the conservation, preservation, and care of local biodiversity. The objective of this research was to see the feasibility of creating a proposal for agricultural tourism activities, in order to improve the economic income of their owners. This study is delimited within a descriptive, documentary, synthetic and analytical research\; it was carried out in four stages: First, a situational technical diagnosis of the areas and components of “D LUCAS” Farm distributes its services, according to the needs and demands of tourists, taking advantage of several agricultural and livestock activities that are carried. Second, the profile of the potential tourist who could visit this agro-tourism microenterprise known as 'D Lucas' Farm was determined, taking into account its characteristics, time for getting relax, motivation, preference if you would like to participate in agro tourism activities. Those were identified, to demonstrate through an economic study the feasibility, sustainability, and profitability of the investment, so the decision is well founded. Finally, the agro tourism activities and strategies that will be promoted in a planned and progressive way were defined, to achieve the satisfaction of tourists, with each of their products and tourist services offered.